An Approach to the Safety Problem of Railway-Road Crossings in the Transport System - Godec, Andrej (Promet - Traffic&Transportation, 2003)
The paper presents an approach to the problem of railway-road level crossings. The goal is to improve safety in thetransport system network, which includes a considerable numberof »inadequately protected« crossings. The single crossing,in its abstract sense, is considered to be a system consisting offour subsystems: the external world, the crossing in its strictsense of the word, the railway and the road. The system analysisof the problem is based on an exhaustive set of bibliography,listed at the end of the paper. This analysis leads to many findingsand those exerting the greatest impact are selected as thebasis for the synthesis. The synthesis proposes a triangle of variables:time period, critical points on the railway network andthe value of the risk indicator. This simple model may includealso other variables by converting relevant values. The main resultis the risk indicator over the network It can be used for variousscenarios, thus enabling their mutual comparison as wellas application in investment studies.